MAY THE ACCUSED (MINISTER OF SAFETY AND SECURITY) PLEASE RISE BEFORE THE COURT: POLICE LIABILITY VERSUS PARTIAL IMMUNITY (The Pretoria Student Law Review, 2021)
This article is written in light of the increasing number of civil actions brought against the South African Police Service (SAPS). Among the most recent cases is that of a Witbank woman and her daughter who instituted an action for damages because an escaped prisoner shot and killed the woman’s husband with a service pistol that the prisoner had stolen from the police. Another related claim is that of Mr Gerber who was shot during an armed robbery at his home in a security complex. Mr Gerber claimed R5.6 million from the Minister of Safety and Security for failing to protect South African citizens. In this article I analyse cases brought against the SAPS. I further illustrate that the state is liable for any delictual act committed by the SAPS, and that the state has a legal duty to protect its citizens and prevent them from harm or any form of violence. However, this does not justify the increasing number of civil actions instituted against the SAPS. My submission investigates whether there is any form of defence on which the state can rely – not to escape liability, but to uphold the functions, duties and reputation of the SAPS. I will argue that the monetary amounts claimed in these civil actions are not in the best interest of the public or that of the SAPS.
Keywords: civil actions; South African Police Service (SAPS); delictual act; escape liability; monetary amounts